Soil biomarkers of cacao tree cultivation in the sacred cacao groves of the northern Maya lowlands. (February 2022) - Terry, Richard E.; Brown, Bryce M.; Stanton, Travis W.; Ardren, Traci; Anaya, Tanya Cariño; Lowry, Justin; León, José Francisco Osorio; Ruíz, Francisco Pérez; Camacho, Nelda Marengo; Magnoni, Aline; Munro-Stasiuk, Mandy; Balzotti, Christopher S.
Highlights: The Ancient Maya tended sacred groves of cacao trees. The shade, moisture and humidity of karst sinkholes supported cacao cultivation. Hot water extraction of soil allows the quantitation of cacao biomarkers: Theobromine; theophylline; and caffeine. Formal staircases, altars, grinding stones, and sherds of incense pots are associated with the sacred groves. Abstract: The importance of cacao in ancient Mesoamerica is attested by the presence of cacao biomarkers in ritual pottery. By at least the Postclassic period, if not earlier, cacao beans are thought to have been a prominent mode of currency in the central Yucatan. During the colonial period the Maya of Yucatan were tending sacred groves of cacao trees in the shaded, humid microclimates of karst sinkholes that dot the peninsula. We report on the development of a method for the extraction and quantitation of the methylxanthine biomarkers of cacao (theobromine, theophylline, and caffeine) from soil. The presence of these biomarkers provides evidence of the distribution and ritual importance of these sacred cacao groves to the Maya. Methylxanthine biomarkers were present in the soils of nine of eleven sampled sinkholes in Yucatan and Quintana Roo, MX.